Zero‐Dimensional Luminescent Metal Halide Hybrids Enabling Bulk Transparent Medium as Large‐Area X‐Ray Scintillators. Issue 10 (3rd March 2022) - Li, Bohan; Xu, Yan; Zhang, Xinlei; Han, Kai; Jin, Jiance; Xia, Zhiguo
Abstract: Scintillators are critical in medical imaging, non‐destructive security screening, and space exploration applications. However, it still remains a challenge to achieve large‐area and high‐transparency scintillators by a low‐cost and easy‐to‐implement way. Herein, a large transparent medium with a diameter over 10 cm is prepared via a facile melt‐quenching strategy using a stoichiometric mixture of ethyltriphenylphosphonium bromide (ETPBr) and MnBr2 as raw materials. Benefiting from the crystallization behavior of high‐efficiency green‐emitting (ETP)2 MnBr4 nanocrystals hybridized with amorphous phase in the transparent wafer, the (ETP)2 MnBr4 ‐based transparent medium as a scintillator evidences a high transparency (over 80%, ranging from 500 to 800 nm), a high light yield of ≈35 000 ± 2000 photon per MeV, a low detection limit of 103 nGy S –1, and a competitive spatial resolution of 13.4 lp mm –1 for X‐ray imaging. This work offers a distinctive simple and fast melt‐quenching methodology to fabricate (ETP)2 MnBr4 metal halide X‐ray scintillator wafer with large‐area and shape flexibility, excellent transparency, and high scintillation performance for the medical or industrial X‐ray imaging application. Abstract : A simple melt‐quenching method is proposed to obtain a high‐efficiency luminescence metal halide transparent medium, for which the crystallization behavior of (ETP)2 MnBr4 nanocrystals (ETP + = ethyltriphenylphosphonium) hybridized with amorphous phase affords its high transparency. The outstanding scintillation performance of (ETP)2 MnBr4 ‐based wafer with large area and shape flexibility holds great promise for X‐ray detection and imaging.